Leading processes to lead companies: Lean Six Sigma Kaizen Leader & Green Belt Handbook - Arcidiacono, Gabriele; Calabrese, Claudio; Yang, Kai.; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2012)
This Minibook is a brief guide for Green Belt during a Lean Six Sigma project management or for Kaizen Leader during a process improvement activity. Through both its theoretical concepts and practical examples it is a pocket book for a quick consultancy. Authors idea comes from companies needs in order to analyze information useful to know in depth different kind of processes. The set of Six Sigma tools are explained through Minitab 16, the last release of the most widely used statistical software.
Keywords: Economics; Engineering economy; Engineering; Endogenous growth (Economics).; Industrial organization (Economic theory).; Economics/Management Science; Industrial Organization; Economics/Management Science, general; Economic Growth; Engineering Economics, Organization, Logistics, Marketing; Facility Management; Administration, Organization and Leadership